Cost-Effectiveness Analysis of New Beta-Lactam Beta-Lactamase Inhibitor Antibiotics Versus Colistin for the Treatment of Carbapenem-Resistant Infections. (February 2022) - Bianchini, Monica L.; Jeffres, Meghan N.; Campbell, Jonathan D.
Introduction: Carbapenem-resistant organisms (CROs) present a serious public health problem. Limited treatment options has led to increased use of colistin and polymyxin. Since 2014, the US Food and Drug Administration approved 4 new beta-lactam beta-lactamase inhibitor (BLBLI) combination antibiotics with activity against CROs. These new antibiotics have been shown to be more effective and less toxic than colistin and polymyxin but are considerably more expensive. This study evaluated the cost-effectiveness of the new BLBLIs versus colistin-based therapy for the treatment of CROs.Methods: A decision-tree microsimulation model was used to evaluate the cost effectiveness of the new BLBLIs versus colistin-based therapy for the treatment of CROs. Treatment groups differed in risk of mortality and risk of an acute kidney injury (AKI). The relative risk of mortality was determined by creating a meta-analysis comparing new BLBLIs to colistin. Cost inputs included medication costs and the cost to treat an AKI. The primary outcomes include quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER). Model inputs included: clinical outcomes and adverse events (30-day mortality and AKI); cost of treatment and adverse drug events; and health utilities. A 3% discount was applied for outcomes. A lifetime horizon was used from the perspective of the US healthcare system with a willingness-to-pay (WTP) threshold of $100 000. A sensitivity analysis was done to incorporate uncertainty.Results: The meta-analysis found the treatment with a new BLBLI was associated with a 50% decrease in the relative risk of 30-day mortality compared to colistin (RR 0.47, 95% CI 0.25-0.88). Treatment with a new BLBLI cost $16 200 and produced 11.5 QALYs, on average. The average colistin based regimen cost $3500 and produced 8.3 QALYs. The new BLBLIs were determined to be cost-effective with an ICER of $3900 per QALY gained. Treatment with a BLBLI remained cost-effective under all uncertainty scenarios tested.Conclusion: New BLBLIs are cost-effective compared to colistin for the treatment of CROs and are associated with improved mortality and fewer AKI events. The use of colistin should be reserved for cases where new BLBLIs are not available or there is documented resistance to these new antibiotics.